Corpus pragmatic studies on the history of medical discourse - Hiltunen, Turo; Taavitsainen, Irma (Pragmatics & beyond ;, 2022)
"The original studies in this volume provide new insights into the history of medical discourse across centuries in both professional and lay texts. The central themes deal with changes in medical writing in various societal and cultural contexts in search for best practices in corpus pragmatics for future work. Some studies apply quantitative methods of corpus linguistics/Digital Humanities, others adopt a qualitative, discourse-analytical perspective, focusing on particular texts, authors or medical topics, or specific functionally-defined discourse forms such as narratives. Quantitative and qualitative approaches are mutually complementary and shed light on different aspects of historical medical discourse. The methodologies aim at establishing validity and reliability for pragmatic analysis, taking into account relevant contextual factors and insights from other fields, such as medical and social history, history of ideas, and science studies"--